Dark matter in a 'Z IND. 3'-symmetry extension of the Standard model - Koerich, Luan Vinícius [UNESP] (2015)
Dark matter accounts for approximately 85% of all the matter in the universe. It is known to have a long lifetime, to be neutral and to interact with ordinary matter almost only gravitationally. There have been several models to suggest possible particles for the dark matter, many of them relying on extensions to the standard model of elementary particles. In particular, there are SIMP (strongly-interacting massive particles) models, which extend the standard model by an extra scalar sector containing the dark-matter particles, whose stability is provided by a discrete symmetry. This symmetry also extends the possible interactions between the dark-matter particles to beyond the usual pair annihilation and Lee-Weinberg scenario described by the WIMP (weakly-interacting massive particles) models. In our study, we postulate the existence of an extended dark sector with a 'Z IND. 3' discrete symmetry, which is the consequence of a global U(1)DM symmetry breaking. This symmetry allows the semi-annihilation and 3 'SETA' 2 annihilation processes to take place, besides the usual self-annihilation process. We will study each of these three scenarios, solving the respective Boltzmann equations and comparing the correspondent relic abundance to the observed one, in order to verify the liability of each of them. We will start by reviewing important aspects of standard cosmology and presenting our model. Then we will review the numerical solutions for the equations, and present our own results for semi-analytical solutions to the semi- and 3 'SETA' 2 annihilation processes. We will end by presenting our own results on solving the 3 'SETA' 2 Boltzmann equation for a temperature-dependent cross-section, calculated with the CalcHEP package